1992
DOI: 10.1007/bf01744603
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of myocardial ischemia reperfusion injury by calcium channel and calmodulin receptor inhibition

Abstract: Intracellular Ca2+ accumulation is implicated in the pathogenesis of myocardial reperfusion injury. To study approaches designed to modify Ca2+ uptake during coronary revascularization after acute infarction, a pig heart surgical infarct model (left anterior descending artery occlusion for 60 min) was subjected to 60 min hypothermic potassium cardioplegic arrest, followed by 60 min of global reperfusion. Four groups of six hearts each were studied in a randomized manner, i.e., cardioplegia alone (control), car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…CN activity in the heart is increased upon ischemia [49]. Consistently, inhibiting CALM could alleviate myocardial ischemia reperfusion injury [44]. These facts suggest important roles of JNK, CN and CALM in the therapeutic action of AGS-IV against myocardial ischemia.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…CN activity in the heart is increased upon ischemia [49]. Consistently, inhibiting CALM could alleviate myocardial ischemia reperfusion injury [44]. These facts suggest important roles of JNK, CN and CALM in the therapeutic action of AGS-IV against myocardial ischemia.…”
Section: Resultsmentioning
confidence: 79%
“…In fact, these pathways have been reported as suitable target pathways for cardiovascular disease therapies [42], [43]. We constructed a myocardial ischemia associated pathway (Figure 4D) by integrating pathways reported to be involved in the process of myocardial ischemia injury, including the calcium signaling, MAPK, JAK-STAT and NF-KB pathway [44][47]. Four targets for approved CVD drugs, ACE, EGFR, CALM and NOS3, are linked with this pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary artery occlusion-induced myocardial ischemia commonly causes ischemic arrhythmias which are the main mortality factor for patients with coronary heart diseases. Calcium, potassium, and sodium channels are totally involved in the initiation and development of ischemic arrhythmias [17,18]. Many studies also showed that calcium and sodium currents were markedly upregulated in heart infarction [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Ca 2+ channel blockers such as verapamil or nifedipine have been shown to reduce ischemia-reperfusion injury when administered before, but not after cardioplegic arrest [6,7]. In previous studies by our group, initial reperfusion with 2,3-butanedione monoxime (BDM), a negative inotropic and vasodilating agent, improved myocardial recovery after cardioplegic arrest [8,9].…”
mentioning
confidence: 99%